Anatomia di uno sdegno - Tichoniuk-Wawrowicz, Ewa (Romanica Silesiana)
<!–EndFragment–>Written in the wake of the September 11, 2001 attacks, Oriana Fallaci’s pamphlet La rabbia e l’orgoglio has provoked an international discussion, as well as trials on charges of defaming Islam. The journalist, outraged by the incomprehension of both, her position and reality in which terrorism prospers and “Eurabia” is being consolidated more and more, responded to the harsh words of critique with two other pamphlets: La forza della Ragione and Oriana Fallaci intervista sé stessa. L’Apocalisse. Both texts are even richer in examples aimed to demonstrate the Islamic expansion, the “presumed” culture of Muslims, and the myopia of European governments, EU and international structures. Fallaci remained true to herself and her own style — direct, expressive, passionate, often offensive — which, combined with her specific views, has provoked attacks, insults and outrage, as well as a wave of admiration. Only time will show if her concepts were indeed prophetic, or simply xenophobic. Key words: Fallaci, Eurabia, Islam, expansion, pamphlet.